Personalized Nanocomposite-based Drug Delivery Systems: Integration of AI and 3D Printing - Aundhia, Chintan; Parmar, Ghanshyam; Talele, Chitrali; Kumari, Mamta; Gupta, Gaurav (Current Drug Targets, 2026)
<span class=
Keywords: 3D printing